Gestão participativa no Ceará: análise dos comitês das sub-bacias hidrográficas do baixo e médio Jaguaribe - Moreira, Tereza Maria Ximenes (2013)
The state of Ceará was one of the pioneers on the national scene to establishits state legislation through the Law No. 11.996/1992, updated by Law No.14.844/2010, which had the legal and institutional basis, SRH and COGERH, SIGERH components, which implemented the water management by watershed, as well as the shared management model, focusing on the partnership between State and Society. The research had focused on the Jaguaribe Watershed, punctually, on the Committees of the Sub-Watershed of the Lower and Middle Jaguaribe, which aims to conduct a comparative analysis of the similarities and differences of these two Committees. They were made in the same period, but they have noticeable differences in operation, in the level of participation of its members in referrals and the deliberations of meetings, among others. Because of these differences that are relevant, this work aims to conduct an analysis of the social dynamics of these committees, investigating the following aspects: management of water resources in the watersheds; charging for water use; conflict over water use; social participation and social networks. The methodology is a quantitative / qualitative approach , focusing on the collegiate , the research universe . At the conclusion of the study it was observed, with regard to the Committees, that despite the differences that have always existed between them , in the eyes of the researcher , the magnitude of these differences is presented in a much larger form , a crystallized impression. After tabulating the data , these differences were regarded in another way . Each committee makes its own way: in some respects they are similar, in others they diverge . Therefore the Committees met when presented the following points in common : lack of financial support for the implementation of projects , which implies greater autonomy ; difficulty of civil society organizations to participate in committee meetings for lack of transport ( today is balanced) and differed on other points as the spatial distance between the municipalities of the watershed , contrasting the realities of the valley and the ' dry area' which has different interests , and the lack of a culture of participation.